2012
DOI: 10.3389/fendo.2012.00172
|View full text |Cite
|
Sign up to set email alerts
|

Testicular cancer and HPV semen infection

Abstract: Testicular cancer represents the more frequent solid tumor affecting males aged 15–35 years. In the last decades, its incidence showed a progressive increased probably due to genetic and environmental factors. Despite exposure to some viruses such as HIV, HCV, EBV, and HPV is frequently related to cancer development, there are no studies aimed to evaluate the possible implication of viral infections in the pathogenesis of testicular cancer. In this study, we analyzed sperm parameters and prevalence of HPV on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 29 publications
1
33
0
3
Order By: Relevance
“…While a causal role has not yet been established for some cancers, a link has been proposed between HPV type 18 and prostate cancer, 33 HPV, EBV and the mouse mammary tumor virus (MMTV) and breast cancer, 34 HPV semen infection and testicular cancer, 35 and polyomaviruses and bladder cancer. 36 In our study, increased risks of prostate cancer, testicular cancer and bladder cancer were seen.…”
Section: Discussionmentioning
confidence: 99%
“…While a causal role has not yet been established for some cancers, a link has been proposed between HPV type 18 and prostate cancer, 33 HPV, EBV and the mouse mammary tumor virus (MMTV) and breast cancer, 34 HPV semen infection and testicular cancer, 35 and polyomaviruses and bladder cancer. 36 In our study, increased risks of prostate cancer, testicular cancer and bladder cancer were seen.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the cancers have been associated with an infectious etiology in HIV-infected adults 1 and children 10 . Although a causal role has not yet been established for some cancers, human papilloma virus (HPV) infection has been associated with lung cancer 11 and testicular cancer 12 in adults.…”
Section: To the Editorsmentioning
confidence: 99%
“…Garolla et al () found a higher prevalence of HPV in the semen of 155 testicular cancer patients compared to controls. They observed that patients who received radio‐ and/or chemotherapy had significantly higher HPV prevalence rates compared to untreated patients (Garolla et al, ). The increased prevalence after treatment might be due to the decreased clearance of the HPV infections because the immune system might have been inhibited by the cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Since HPV is known to cause malignancy in the female Cervix uteri and in the anus, penis and pharynx (Garolla et al, ), it is reasonable to ask whether HPV is a cause of testicular cancer. Garolla et al () found a higher prevalence of HPV in the semen of 155 testicular cancer patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation